2015
DOI: 10.1053/j.gastro.2014.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Unique Genomic Profile of Fibrolamellar Hepatocellular Carcinoma

Abstract: Background & Aims Fibrolamellar hepatocellular carcinoma (FLC) is a rare primary hepatic cancer that develops in children and young adults without cirrhosis. Little is known about its pathogenesis, and it can only be treated with surgery. We performed an integrative genomic analysis of a large series of patients with FLC to identify associated genetic factors. Methods Using 78 clinically annotated FLC samples, we performed whole-transcriptome (n=58), single-nucleotide polymorphism array (n=41), and next-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
131
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(147 citation statements)
references
References 60 publications
(66 reference statements)
8
131
2
6
Order By: Relevance
“…The recent development of the next-generation sequencing technologies provides novel strategies for analyzing the human genome and epigenome. Use of these new technologies has gradually begun to unveil the landscape of genetic and epigenetic aberrations of a variety of human tumors, including HCC [19][20][21][22][23][24][25][26][27][28][29][30]. In this article, we review the recent findings concerning genetic and epigenetic aberrations that accumulate during the development of hepatitis virus-associated HCC.…”
Section: Introductionmentioning
confidence: 99%
“…The recent development of the next-generation sequencing technologies provides novel strategies for analyzing the human genome and epigenome. Use of these new technologies has gradually begun to unveil the landscape of genetic and epigenetic aberrations of a variety of human tumors, including HCC [19][20][21][22][23][24][25][26][27][28][29][30]. In this article, we review the recent findings concerning genetic and epigenetic aberrations that accumulate during the development of hepatitis virus-associated HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in the Cornella et al study, which reported on 77 FLC, the presence of fusion transcript was found in 79% of cases. 5 Conversely, in the Graham et al study, rearrangements of the PRKACA locus were seen in all 19 FLC cases (100%). 9 Beside the specificity of DNAJB1-PRKACA transcript in support of diagnosis of FLC, the role of epigenetics alterations in shaping FLC identity and distinguishing p-FLC from other HCC subtypes remains limited.…”
Section: Introductionmentioning
confidence: 80%
“…4 Using transcriptomic profiling of a large set of p-FLC, m-FLC and HCC arising in non-cirrhotic liver, we and others recently showed that p-FLC harbor a unique signature characterized by the strong expression of specific neuroendocrine genes (i.e., PCSK1, DNER, CALCA and NTS). [5][6][7] Meanwhile, a recurrent DNAJB1-PRKACA chimeric transcript has been identified in a data set of 15 FLC cases (100%) suggesting that this genetic alteration contributes to tumor pathogenesis. 8 However, whether this translocation is pathognomonic for the diagnosis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is by far the most prevalent type, accounting for approximately 80%-85% of primary liver cancer cases (Singal and El-Serag, 2015), whereas cholangiocarcinoma (Ghouri et al, 2015) and fibrolamellar carcinoma (Lim et al, 2014;Cornella et al, 2015) occur at a frequency of only ∼14% and ∼1%, respectively. The epidemiology of HCC is well known, and in the vast majority of cases, it arises as a consequence of underlying liver disease, usually a viral hepatitis (Singal and El-Serag, 2015).…”
Section: Introductionmentioning
confidence: 99%